2019
DOI: 10.9734/asrj/2019/v2i230049
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Homegarden Agroforestry Systems for Climate Change Mitigation in Lowlands of Southern Tigray, Northern Ethiopia

Abstract: Mitigation of climate change is one of the major environmental challenges facing the globe. In this context, homegarden agroforestry systems (HGAFs) have large potential for climate change mitigation. Therefore, this study was initiated to estimate the biomass and soil carbon stocks of HGAFs in relation to adjacent Natural Forest (NF). It also analyzed the relationship between woody species diversity, evenness and richness with biomass and soil carbon stocks. Three sites were purposely selected on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
2
2
2
Order By: Relevance
“…However, the AGC stock in the homegarden agroforestry was nine times higher than the previous report [ 37 ]. Similarly, the AGC stock of the HGAF of the study area was higher than that of the protected natural vegetation from northern Ethiopia [ 62 ], but similar to the findings from the agroforestry system in the Lowlands of Northern Ethiopia [ 67 ], as well as church forests [32.]. On the other hand, the biomass carbon stock values of the exclosure in the present study were lower than Jabitehnane district in Ethiopia [ 38 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the AGC stock in the homegarden agroforestry was nine times higher than the previous report [ 37 ]. Similarly, the AGC stock of the HGAF of the study area was higher than that of the protected natural vegetation from northern Ethiopia [ 62 ], but similar to the findings from the agroforestry system in the Lowlands of Northern Ethiopia [ 67 ], as well as church forests [32.]. On the other hand, the biomass carbon stock values of the exclosure in the present study were lower than Jabitehnane district in Ethiopia [ 38 ].…”
Section: Discussionsupporting
confidence: 81%
“…The depth from 0 to 60 cm for SOC stocks of HGAF in the present study is lower than indigenous agroforestry systems on the south-eastern Rift Valley escarpment (173–373 Mg ha −1 ) [ 34 ]. However, it was higher than a report (mean: 109.75 ± 29.95 Mg ha −1 ) from Northern Ethiopia [ 67 , 74 ], as well as from India [ 74 ]. On the other hand, the surface layer (0–30 cm) SOC stocks of HGAF in the study area were lower than in previous reports [ 33 , 34 , 66 ].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Also extensive reviews were carried out by [8] for "West African countries (extending from Arid Sahara Desert to humid region Guinea) and they reported that biomass C stocks ranged from 22.2 to 70.8 t C ha −1" . "There are many similar studies conducted in various regions of the continents" [9]. "From global report, the total biomass C stock for agroforestry systems ranges between 12 and 228 t C ha −1" [1,10] also reported that "agroforestry practices stored C ranging from 0.29 to 15.21 t C ha −1 yr −1 in their aboveground biomass and can have from 30 to 300 t C ha −1 in their soil down to one-meter depth.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive reviews by [13] for West African Sahel countries (extending from arid Sahara Desert to humid region Guinea) reported biomass C stocks ranging from 22.2 to 70.8 t C ha −1 . There are many similar studies conducted in various regions of the continents [14][15][16][17]. As reports showed globally, the total biomass C stock for AF systems ranges between 12 and 228 t C ha −1 [10,18].…”
Section: Introductionmentioning
confidence: 99%